Construct validity of writing motivation questionnaire - Devdulal Dutta Roy (Universidad de San Buenaventura, 2010)
The article reports results of two consecutive studies designed to understand construct validity of writing motivation and to examine its utility in the prediction of academic achievement. In first study, data were collected from 884 students of primary education through writing motivation questionnaire with seven domains (Dutta Roy, 2003). Correspondence analysis reveals two latent traits (intrinsic and extrinsic) of writing motivation. In the second study, writing motivation questionnaire was administered to 200 students and their academic performances in schools were collected. Results reveal inverse relation between latent traits. Composite scores of intrinsic writing motivation were positively and those of extrinsic writing motivation were negatively correlated with academic performance.